2014
DOI: 10.1186/1471-2261-14-159
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum free fatty acid levels and possible related factors in patients with type 2 diabetes mellitus and acute myocardial infarction

Abstract: BackgroundFree fatty acids (FFAs) play importance roles in the development of diabetes and cardiovascular diseases. We measured serum FFA levels from type 2 diabetes mellitus (T2DM) and acute myocardial infarction (AMI) patients and assay the correlation between serum FFA levels and related factors. The present study was undertaken to investigate a possible relation between the changes in serum free fatty acid concentration with acute myocardial infarction and type 2 diabetes mellitus.MethodsThe study populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…There was no any statistically significant association between the HbA1c level and the uric acid level in any of our study groups. Higher glucose was seen in AMI cases in Lv et al 20 In this study, we can say that the serum uric acid level on raise with increase in fasting plasma glucose in group I, but seems to be decreasing in group II. This was found to be similar with Cirakli ZL et al 17 and Nan H et al 21 studies.…”
Section: Discussionsupporting
confidence: 50%
“…There was no any statistically significant association between the HbA1c level and the uric acid level in any of our study groups. Higher glucose was seen in AMI cases in Lv et al 20 In this study, we can say that the serum uric acid level on raise with increase in fasting plasma glucose in group I, but seems to be decreasing in group II. This was found to be similar with Cirakli ZL et al 17 and Nan H et al 21 studies.…”
Section: Discussionsupporting
confidence: 50%
“…The data presented in the present study demonstrated that PA promotes MDA-MB-231 cell apoptosis and invasion while OA promotes proliferation, migration and invasion. Although FFA levels are generally elevated in breast cancer patients ( 19 , 20 ), the role of FFA in health and disease in humans has been minimally investigated and understood.…”
Section: Discussionmentioning
confidence: 99%
“…An elevated FFA concentration is linked to several risk factors for atherosclerosis (5), including acute myocardial infarction (17), cardiovascular disease (8), heart failure (10), and atrial fibrillation (AF) (16). Pathological processes, including ischemia and subarachnoid hemorrhage, result in significant increases in brain concentrations of free fatty acids (FFAs) in animal studies (13).…”
Section: Introductionmentioning
confidence: 99%